1980
DOI: 10.1128/jvi.33.3.1138-1150.1980
|View full text |Cite
|
Sign up to set email alerts
|

Late modifications of simian virus 40 chromatin during the lytic cycle occur in an immature form of virion

Abstract: Two main modifications of the simian virus 40 chromatin were found to occur during the lytic cycle. One was the progressive increase in the acetylation level in the four non-H1 histones as the 75S deoxynucleoprotein complexes (minichromosomes) became assembled into heavier structures. The other was the final elimination from viral chromatin of histone H1. An important stage in the course of these changes was represented by an intracellular simian virus 40 particle, in which the virus-coded proteins were alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
22
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 27 publications
4
22
0
Order By: Relevance
“…Analysis of SV40 tsB and BC capsid protein mutant viruses have shown that aberrant nucleoprotein intermediates accumulate at the nonpermissive temperature for growth, which is consistent with the incremental addition model (5,34). Coincident with VP1 addition, histone Hi is lost from the minichromosome, suggesting that capsid protein binding may occur in the internucleosomal DNA, displacing Hi (12,27). Experiments demonstrating a change in the internucleosomal spacing of viral chromatin during infection with SV40 temperature-sensitive VP1 mutant viruses support a direct interaction of the capsid proteins with the viral chromatin (6).…”
supporting
confidence: 62%
“…Analysis of SV40 tsB and BC capsid protein mutant viruses have shown that aberrant nucleoprotein intermediates accumulate at the nonpermissive temperature for growth, which is consistent with the incremental addition model (5,34). Coincident with VP1 addition, histone Hi is lost from the minichromosome, suggesting that capsid protein binding may occur in the internucleosomal DNA, displacing Hi (12,27). Experiments demonstrating a change in the internucleosomal spacing of viral chromatin during infection with SV40 temperature-sensitive VP1 mutant viruses support a direct interaction of the capsid proteins with the viral chromatin (6).…”
supporting
confidence: 62%
“…Analyses of the level of acetylation of histones in the different SV40 DNA-protein complexes have shown that the histones in chromatin are underacetylated relative to those in previrions and virions (2,10,16). It is possible, using a short pulse of radiolabeled acetate, to show that the label first appears in chromatin and then in previrions and virions (2,10). Wang and I (20) and Coca-Prados et al (2) have therefore proposed that the level of acetylation of histones may be a critical factor in determining whether the viral DNA remains in the replication pool or enters the maturation pathway.…”
mentioning
confidence: 99%
“…forms (26,66). The 75S particle is not infectious, whereas 200S-240S particles are (4,42). The 200S and 240S species usually comigrated; however, a distinct 200S species could sometimes be discerned at early times over the course of pulse-chase (21,23), and this species appeared to be sensitive to high salt concentrations and unstable when recentrifuged in CsCl gradients (4,19,33,43,57).…”
Section: Discussionmentioning
confidence: 99%
“…Some confusion has centered over the specific order and stages in which capsid proteins are added to assembly intermediates. Over the course of virion assembly, histones H2A, H2B, H3, and H4 become more highly acetylated, apparently by protection from deacetylase activity, and histone Hi is displaced or degraded, such that it appears in 75S and 200S particles but not in virions (13,14,21,42,43). This proceeds concurrently with the progressive addition of VP1, VP2, and VP3 to the 75S viral minichromosome.…”
Section: Discussionmentioning
confidence: 99%